1997
DOI: 10.1084/jem.185.12.2101
|View full text |Cite
|
Sign up to set email alerts
|

Altered Immune Responses in Interleukin 10 Transgenic Mice

Abstract: Interleukin (IL)-10 is a pleiotropic cytokine which inhibits a broad array of immune parameters including T helper cell type 1 (Th1) cytokine production, antigen presentation, and antigenspecific T cell proliferation. To understand the consequences of altered expression of IL-10 in immune models of autoimmune disease, the response to infectious agents, and the response to tumors, we developed transgenic mice expressing IL-10 under the control of the IL-2 promoter. Upon in vitro stimulation, spleen cells from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
151
0
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(161 citation statements)
references
References 42 publications
8
151
0
2
Order By: Relevance
“…Regulation of autoreactivity in the priming phase by IL-10 is consistent with the finding that supplementation of IL-10 prevented the development of colitis in IL-10-deficient mice (48) or in the CD45RB high transfer model (22,23). IL-10 also suppressed autoreactivity in the secondary culture.…”
Section: Figuresupporting
confidence: 87%
“…Regulation of autoreactivity in the priming phase by IL-10 is consistent with the finding that supplementation of IL-10 prevented the development of colitis in IL-10-deficient mice (48) or in the CD45RB high transfer model (22,23). IL-10 also suppressed autoreactivity in the secondary culture.…”
Section: Figuresupporting
confidence: 87%
“…Therefore, one might predict that IL-10 would also play a role in the suppression of antitumor immunity. Indeed, transgenic mice expressing IL-10 under the control of the IL-2 promoter are compromised in their ability to reject experimental lung carcinomas, while IL-10-deficient mice mount more potent Th1 and CTL responses against bladder tumors and melanomas (16,17). Furthermore, murine plasmacytomas treated with antisense IL-10 are more immunogenic than the parental cell lines (18).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed that the protective effect was dependent on TGF-␤ and/or IL-10 (14,(17)(18)(19)(20), but not on IL-4 (18).…”
mentioning
confidence: 96%